Development of pathological tremor cancelling for human-machine interaction - Fariadi, Yulius Setiadi (2010)
The project investigates the collaboration in human-machine interaction for the control system of robot with joystick as the user input interface. The purpose of this project is to implement an online pathological tremor cancelling method in hu-man-machine interaction.